PENGARUH ASPEK FISIK DAN ADMINISTRASI BIAYA TERHADAP KUNJUNGAN PASIEN KE RUMAH SAKIT GIGI DAN MULUT (RSGM) UNIVERSITAS JEMBER ANTARA PASIEN MAHASISWA DAN PASIEN UMUM - Kiswaluyo Kiswaluyo; Zahara Meilawaty; Budi Prabowo (Fakultas Kesehatan Masyarakat, Universitas Jember, 2010)
The patients coming to Dental Hospital Jember University are those brought by dental students and those coming by their own will. Most patients come to the Dental Hospital because they are asked by the students to fulfill their academic requirements. The purpose of this study is to figure out the influence of physical and fee administration aspects of the Dental Hospital Jember University between the patients brought by the students and those who come by their own will. This study used a descriptive and analytic method with cross-sectional approach. The samples were taken from the patients visiting Dental Hospital Jember University. The result of this study was analyzed using Mann Whitney U Test. It was showed that there was a significant difference on the physical of Dental Hospital, while on there was no significant difference in the aspect of administrative fee both in common patients and those brought by the students. Keywords : The factors affecting the visit, patients brought by students, common patients